Physical activity and inactivity in primary and secondary school boys' and girls' daily program - Romana Hubáčková; Dorota Groffik; Lukasz Skrzypnik; Karel Frömel (Palacký University Olomouc, 2016)
Background: Children's and youth education is becoming more and more demanding. In conjunction with development of information technology, this fact negatively affects lifestyle of children and youth. Apart from families, schools should play a crucial role in healthy lifestyle promotion in children and youth. Objective: The present study aimed to assess differences in physical activity (PA) and physical inactivity (PI) among primary and secondary school boys and girls in specific segments of a school day. Methods: The research was conducted between 2010 and 2014 at 15 secondary schools (SS) and 9 primary schools (PS) in the Silesia-Katowice region in Poland. In total, 86 boys and 71 girls at PS and 125 boys and 113 girls at SS took part in the research. We recorded 587 school days, in total. The ActiTrainer accelerometer was used for PA and PI monitoring. Results: PS boys and girls were more physically active than SS boys and girls. Before school, we observed SS boys to have higher energy expenditure than PS boys (p < .001) and also than SS girls (p < .001). During the school time, 73% of PS boys (40% at SS) and 58% of PS girls (42% at SS) met the recommendation of 500 steps/hour. Within the entire school day monitoring, 44% of PS boys (29% at SS) and 41% of PS girls (34% at SS) met the recommended 11,000 steps/day. Conclusions: The results of our study confirmed the facts that PS boys and girls are more physically active than SS boys and girls and, furthermore, that boys are more physically active than girls at both types of schools.